A Study on the Economic Sustainability of Local Coffee Production in the Philippines - Ysabelle Luat; Julia Mendoza; Mark To; Ronaldo Cabauatan (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2021)
The coffee has been a major source of income for centuries now, it sure does contribute to the country’s productivity, specifically agricultural sectors. This study seeks to identify whether the local coffee production can keep up with the rising demand for coffee in the Philippines. The country's local coffee production is examined to know whether it will be a sustainable source for the country's coffee industry in the long-run and whether its production would be a good investment for several companies. This study determines the impact of local coffee consumption to the shortage of local coffee beans and surplus in the demand for coffee in the country. Furthermore, by using a time series regression analysis, the study determines whether the local coffee production has positive or negative effects on each variable. Using the gathered data from different academic references, this study identified the relationship of the local coffee production among each variable.